Cerita Rakyat “Saliwu, Pahlawan Suku Padoe” - nfn Mustafa (Madah: Jurnal Bahasa dan Sastra, 2018)
This study aims to research Luwu's oral literary work on the character of the story based on the Levi-Strauss analysis model. "Saliwu, Pahlawan Suku Padoe" is one of the literary works of the Luwu community which is full of values and concepts of life, delivered orally, and passed down from generation to generation to speakers. This story tells about a great king's who struggle with high self-esteem against the oppression of other ethnic group who wished to dominate and colonize their region. In addition, the story can be a source of advice and learning for posterity for the provision of the coming day so that it does not get lost. This story also intends to introduce a character who is described as a great hero and highly respected. He is willing to be held captive and die in exile rather than betraying his people who uphold custom. The theory used is Levi-Strauss with descriptive analysis method. The results found indicate that there is structured relationship between elements in the story and social conditions in the community.